What Are the Poverty and Inequality Impacts of Fiscal Policy in Turkey? - Cuevas, P. Facundo (World Bank, Washington, DC, 2020)
Fiscal policy is central to not only macroeconomic stability and growth, but also to poverty and inequality reduction. This paper provides the most comprehensive assessment of the distributional incidence of Turkey’s fiscal policy to date. It analyzes the combined and individual incidence of direct and indirect taxes, transfers, and social spending and benchmarks Turkey’s achievements against peer countries. The results show that fiscal policy significantly reduces income inequality in Turkey, driven by social spending on education and health, and complemented by direct taxes and transfer schemes that countervail the inequality-increasing impact of indirect taxes. At the bottom of the income distribution, targeted transfers are insufficient to compensate for the effect of taxes, resulting in net increases in poverty. In the context of upper-middle-income countries, Turkey’s performance is below the median. This is driven by the relatively larger negative impacts of indirect taxes and the more limited positive impacts of direct transfers and taxes. From a policy perspective, the paper contributes to identifying entry points for improving the equity impact of the fiscal package. Among these, targeting the minimum subsistence allowance (AGI) program toward the poor could be an efficient way forward. More broadly, the study represents a platform to simulate the distributional implications of a variety of fiscal changes to inform stakeholders and the policy debate.